Iran - O'Shea, Maria (Milwaukee, Wisconsin Gareth Stevens Pub, 2000)
An introduction to the geography, history, government, lifestyles, culture, and current issues of Iran.
Includes bibliography references and Index
10 years and up
Keywords: Iran